Les charpentes à entrait retroussé moisé : exemples orléanais des XVe et XVIe siècles - Clément Alix; Julien Noblet (Revue Archéologique du Centre de la France)
The town of Orleans possesses an important and unpublished collection of timber-framed roof structures of the 15th and 16th centuries, with a braced collar-beam. Known since the first quarter of the 15th century, this innovative process, involving two twinned pieces clasping the main elements of the frame, became widely spread in religious buildings but particularly in domestic housing, from the multipurpose timber-framed home to the elaborate town house. This method of construction, demonstrating a perfect mastery of the statics of a roof structure from its design with a view to reinforcing the triangulation of the truss, rapidly established itself in a local architectural context marked by the rare use of “chevrons-formant-fermes” (common rafters forming a bent). It is also found in roof structures such as turret staircases, pavilion roofs, and apses. The widespread use of the brace in Orleans, and in a more limited manner in the Val de Loire and in certain regions of France, leads us to question the origins of this process, which is known in other forms of roof structures in the 12th-13th centuries.Carpentry, building archaeology, urban residence, Middle Ages, Renaissance